Directed Search with Phantom Vacancies - James Albrecht; Bruno Decreuse; Susan Vroman (Institute of Labor Economics (IZA), 2020)
When vacancies are filled, the ads that were posted are often not withdrawn, creating "phantom" vacancies. The existence of phantoms implies that older job listings are less likely to represent true vacancies than are younger ones. We assume that job seekers direct their search based on the listing age and so equalize the expected benefit of a job application across listing age. Forming a match with a vacancy of age α creates a phantom of age α with probability β and this leads to a negative informational externality that affects all vacancies of age α and older. Thus, the magnitude of this externality decreases with the age of the listing when the match is formed. Relative to the constrained efficient search behavior, the directed search of job seekers leads them to over-apply to younger listings. We illustrate the model using US labor market data. The contribution of phantoms to overall frictions is large, but, conditional on the existence of phantoms, the social planner cannot improve much on the directed search allocation.
Keywords: J60; D83; 330; directed search; phantom vacancies; unemployment